Accounting Studentsâ Choice on Accounting Information Technology Careers - Dewi, Nurul Hasanah Uswati (Universitas Prasetiya Mulya, 2014)
The important role of accounting information systems professionals, motivate researchers to analyze further the interest of students to the profession in the field of accounting information systems. The aim of this study explores the factors that influence students to choose and do not choose a profession in the field of accounting information systems. This research was conducted using questionnaires. The population was undergraduate accounting students. Sample research was done randomly. This research shows that the interest in undergraduate accounting students for a career in the field of information systems is very small and this research also appears that the academic supervisor is one of the dominant factors influencing student choice in choosing a career in the field of information systems. Beside this, this study also found that respondents are not interested in a career in accounting information systems more due to that field of information systems is not a career they aspire.DOI :Â https://doi.org/10.21632/irjbs.7.3.178-188Keywords: Accounting Information System, Accounting Career, Students